Sleep quality, affect, pain and disability in children with chronic pain: Is affect a mediator or moderator? - Evans, Subhadra (J Pain, 2017)
Sleep problems have been identified as a potential antecedent of chronic pain and pain-related disability in pediatric populations. In adult studies, affect has been implicated in these relationships. This study sought to better understand the relationships between sleep quality, negative and positive affect and pain and functioning in children with chronic pain. Participants included 213 children and adolescents (aged 7–17) presenting to a tertiary pain clinic with chronic pain. Children completed questionnaires measuring sleep quality, positive and negative affect, pain intensity, and functional disability. Results indicated that 74% of children reported disordered sleeping and that poor sleep quality was significantly associated with increased pain, disability, negative affect, and decreased positive affect. Our hypotheses were partially supported, with negative affect (but not positive affect) mediating the relationship between poor sleep and increased pain; and both positive and negative affect mediating the relationship between poor sleep and increased functional disability. There was no evidence for affect as a moderator. This study adds to the growing literature demonstrating the impact of poor sleep quality on children’s pain and functioning, highlighting the need to develop further longitudinal research to confirm the causal roles of these variables.